JARGON IN ENGLISH PARLIAMENTARY DEBATING - Ni Kadek Ary Susandi; Furqanul Hakim; Ni Wayan Novi Suryati (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
The fact that language changes is indisputable and inevitable. The nature of language that is very dynamic - following the development of the society leads to the emergence of linguistics variation. Linguistics variation is believed to rely heavily on people’s live and interactions. Hudson states (1981: 25) “the defining characteristic of each variety is the relevant relation to society – in other words, by whom, and when, the items concerned are used”. The present study examines the differences in variations of the language used by the people in a particular group – the forms, meaning and function of English jargons used by University students competing in English parliamentary debating competitions held in the region Bali, West and East Nusa Tenggara, Indonesia. Jargon is a collection of words or specific terms used by a group of people, in which the words are only understood by those who joined the group (Fromkin and Rodman, 1979). The data were collected by recording the speech delivered by debaters during debating at the tournaments and interviewing the debaters to clarify the meaning and function of jargons used. The data will then be analyzed descriptively based on sociolinguistics and language variations theories, also previous related studies. This research is beneficial to increase scientific vocabularies and can be used as references for English teachers or English debate coaches to develop their students’ skills in using English and/or to improve students’ achievement in the field of English debating.